Estudio de factibilidad para la creación de una empresa de vestimenta típica del sector Afro-Choteño ubicado en Imbabura y Carchi - Espinoza Viveros, Mileydi Soraya (2023)
The present study was carried out because there is a business opportunity in the market and to supply an offer that in a certain sense has become lacking in the afrochoteño people, which is not a need that directly satisfies the expectations of the new generations, but to the recovery of traditions and cultures, making the country multi diverse and multicultural. In this way, in order to know the feasibility for the creation of a company of the typical clothing of the Chota Valley located in Imbabura and Carchi, it was considered to approach with the results of market, technical, organizational and financial studies, carried out in a mixed approach - quantitative and qualitative - collecting data with numerical, non-numerical, oral and observational expression of transversal cut and non-experimental design. The economic activity of the company is the manufacture of clothing oriented to the afrochoteño sector, mentioning that acceptance was obtained in the project.